2020
DOI: 10.1038/s41598-020-73151-8
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of glymphatic–lymphatic drainage of beta-amyloid by focused ultrasound in Alzheimer’s disease model

Abstract: Drainage of parenchymal waste through the lymphatic system maintains brain homeostasis. Age-related changes of glymphatic–lymphatic clearance lead to the accumulation beta-amyloid (Aβ) in dementia models. In this study, focused ultrasound treatment in combination with microbubbles (FUS-MB) improved Aβ drainage in early dementia model mice, 5XFAD. FUS-MB enhanced solute Aβ clearance from brain, but not plaques, to cerebrospinal fluid (CSF) space and then deep cervical lymph node (dCLN). dCLN ligation exaggerate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
59
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(64 citation statements)
references
References 24 publications
(36 reference statements)
5
59
0
Order By: Relevance
“…Despite the evidence of water clearance by FUS–BBBD ( Meng et al, 2019 ; Lee et al, 2020 ), the water dynamics in the local sonication region have yet to be ascertained. Here, we aimed to explore whether FUS–BBBD could induce local water diffusivity changes, which would provide preliminary support for understanding the underlying mechanisms of waste clearance by FUS–BBBD.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Despite the evidence of water clearance by FUS–BBBD ( Meng et al, 2019 ; Lee et al, 2020 ), the water dynamics in the local sonication region have yet to be ascertained. Here, we aimed to explore whether FUS–BBBD could induce local water diffusivity changes, which would provide preliminary support for understanding the underlying mechanisms of waste clearance by FUS–BBBD.…”
Section: Discussionmentioning
confidence: 99%
“… Meng et al (2019) showed that the MR contrast agent can be delivered to the brain parenchyma, and further observed clearance in the interstitial fluid pathway through the perivenular and subarachnoid spaces, as well as around draining veins. Lee et al (2020) demonstrated that FUS–BBBD enhances the glymphatic clearance of Aβ mainly by increasing brain-to-CSF drainage. This glymphatic dynamic may be related to biological effects induced by mechanical forces; however, the subsequent changes in water dynamics in the local perivascular region are yet to be clearly established ( Burgess et al, 2012 ; Meng et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These enzymes typically have targets other than Aβ so understanding how their regulation fits in to the wider proteome is crucial to understanding their role in AD and their viability as therapeutic targets. In addition to enzymatic degradation, Aβ is also cleared by interstitial fluid drainage and drainage through the glymphatic system (see Jessen et al, 2015;Yoon and Jo, 2012) with recent studies in the 5XFAD mouse model interestingly showing this can be promoted by ultrasound (Lee et al, 2020). AD-sufferers exhibit reduced CSF levels of Aβ42, an observation that confers this measure as a predictive biomarker, albeit not as well as the ratio of Aβ42 to Aβ40 (Hansson et al, 2019;Holtzman, 2011).…”
Section: Control Of Aβ Aggregationmentioning
confidence: 99%